CCENS: Centro de Ciências Exatas e da Saúde - dos Santos Oliveira , Daniel; Terra Decupero , Vívian; Damascena Cardoso , Caroline; Santos Pinheiro Coelho , Elisa; Pirola Madeira , Klesia; de Mello Silva, Betyna Clara; Fortunato Barbosa, Joyce; Scardini Neves, Lucas; Simoes Pereira , Lorena; Amorim Ribeiro , Isabela; Alves , Jadyna Aparecida; Crisostomo Santos, Nandyala; et al. (Guará Journal, 2023)
Resumos dos projetos do Centro de Ciências Exatas e da Saúde